Motivation of student teachers in educational psychology course - Puklek Levpušček, Melita (Psihološka obzorja (Ljubljana), 2007)
The study examined various aspects of student teachers' initial motivation for educational psychology course and the effect of motivation on student teachers' engagement in a specific academic activity and on the final course achievement. At the beginning of the academic year 2004/2005 undergraduate student teachers filled in the Motivated strategies for learning questionnaire (MSQL, Pintrich et al., 1991), the part assesses students' motivational orientations. During the academic year students prepared and then presented to their colleagues their seminar work in groups. After each presentation, members of the group assessed the quality of their individual preparation, analyzed the quality of group work and assessed their part of the seminar presentation. Students' achievement was measured by an exam after completing the entire educational psychology course. The results showed that those students who had found the educational psychology course interesting and useful, and who had participated in the course because of extrinsic reasons prepared seminar work better and assessed their seminar presentation with higher marks than those with low motivation for the course. Students' engagement in individual study and self-assessment of seminar presentation were related to the final course grade. In addition, students' perception of the course as interesting and useful (task value) independently predicted final course grade, over and above the account of previous academic achievement.
Keywords: učna uspešnost; motivacija; motivation; psihologija za učitelje; student; študenti